Why Treat When You Can Prevent? : Preventive Dentistry - Shah, Rohit; Khatri, Humera; Mitra, Dipika; Talati, Meenakshi; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Tooth decay is often called the second most prevalent human disease after common cold. Without effective treatment it can lead to pain, tooth loss or even hamper your smile. It is rightly said, ‘PREVENTION IS BETTER THAN CURE’. A major role in decay prevention is to tip the balance in favor of the beneficial processes. Preventive dentistry aims to stop the progression of dental caries by promoting daily habits and clinical therapies that either promote the remineralization of the tooth surface or prevent the formation of the oral biofilm responsible for lowering the oral pH levels in an attempt to prevent cavity formation. This review provides a perspective of the mechanisms and clinical efficacy of several traditional preventive dentistry measures and also describes the newer technology that shows promising results in preventing dental caries.